2020
DOI: 10.1128/jvi.01717-19
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of the cGAS-STING and TLR3 Signaling Pathways to Attenuation of Herpes Simplex Virus 1 Replication

Abstract: The innate immune response is crucial for defense against viral infections. Cells recognize virus infection through pattern recognition receptors and induce type I interferons as well as proinflammatory cytokines to orchestrate an innate immune response. Herpes simplex virus 1 (HSV-1) triggers both the cyclic GMP-AMP synthase (cGAS)–stimulator of interferon genes (STING) and Toll-like receptor 3 (TLR3) pathways. It is well known that TLR3 uses the adaptor protein Toll/interleukin-1 receptor (IL-1R) domain-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…cGAS is also upregulated in astrocytes, but not microglia following HSV-1 infections. This suggests that cGAS may also play a role in controlling HSV-1 infections in the central nervous system, but may be species specific [ 83 , 84 , 85 ]. This is further supported in mice with cGAS or STING deficiencies having a higher susceptibility to HSE due to uncontrolled HSV-1 replication in neurons [ 86 ].…”
Section: Recognition Of Hsv-1 By the Innate Immune Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…cGAS is also upregulated in astrocytes, but not microglia following HSV-1 infections. This suggests that cGAS may also play a role in controlling HSV-1 infections in the central nervous system, but may be species specific [ 83 , 84 , 85 ]. This is further supported in mice with cGAS or STING deficiencies having a higher susceptibility to HSE due to uncontrolled HSV-1 replication in neurons [ 86 ].…”
Section: Recognition Of Hsv-1 By the Innate Immune Systemmentioning
confidence: 99%
“…TLR3 deficient astrocytes are susceptible to HSV-2 infections and TLR3 deficient DCs are inefficient in priming CD8+ T cells in response to HSV-1 [ 115 , 116 ]. Neurons and epithelial cell lines that are TLR3 deficient have increased susceptibility to HSV-1 infection [ 84 , 117 ]. However, murine macrophages can compensate for a loss of TLR3 and amount a normal type I IFN response to control HSV-2 infections [ 70 ].…”
Section: Recognition Of Hsv-1 By the Innate Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent findings showed that the function of TLR3 on sensing HSV-1 dsRNA to elicit antiviral immunity remains disputed in various cell types and species [72]. Strikingly, the Sen's group recently revealed that the TRIF could combine cGAS-STING and TLR3 pathways by engaging with both STING and TLR3 to establish a powerfully antiviral state to suppress HSV-1 replication [73]. The contribution of these two pathways in controlling HSV-1 infection is also cell types and species specific.…”
Section: Other Rna-sensing Machinery Detects Dna Virusesmentioning
confidence: 99%